Korelasi antara Full Day School dengan Prestasi Belajar PAI Siswa di SMP Darul Ulum Agung Malang - Muhtadi Muhtadi (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2019)
This study aims to find the correlation between full day school and PAI learning achievement of students in SMP Darul Ulum Agung Malang. This type of research is quantitative descriptive, with data collection techniques of observation, interviews, questionnaires and documentation. The data analysis technique uses the product moment correlation analysis technique. Based on the results of the calculation of x2 shows the value of 0.533 then when consulted with the price of criticism in the household both at a significance level of 1% and 5%. So the results of this study indicate the value of x2, which is 0.533 greater than the rt at the significance level of 1%: 0.418 and the rt value at the significance level of 5%: 0.325. Thus there is a moderate or sufficient correlation between full day school and PAI learning achievement of students in SMP Darul Ulum Agung Malang.